2018
DOI: 10.1016/j.rmed.2018.10.016
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the effect of saffron supplementation on the antibody titer to heat-shock protein (HSP) 70, hsCRP and spirometry test in patients with mild and moderate persistent allergic asthma: A triple-blind, randomized placebo-controlled trial

Abstract: Background: Asthma is a heterogeneous disease, which usually associated with chronic airway inflammation. The anti-heat shock protein (anti-HSP) 70 is a novel risk factor for asthma. The aim of the present study was to survey the effect of saffron supplementation on anti-HSP70, high-sensitivity C-reactive protein (hs-CRP) and spirometry test in patients with allergic asthma. Basic procedures: In this clinical trial, patients (N = 80, 32 women and 48 men, 18-65 years old) with mild and moderate allergic asthma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 14 publications
(29 reference statements)
1
27
0
Order By: Relevance
“…Saffron (Crocus sativus L.) has antioxidant [5], anti-inflammatory [6], and muscle relaxant effects [7] and so has beneficial effects on asthma. Results of our clinical trial showed that saffron supplementation (100 mg of dried saffron stigma in capsules) for 8 weeks in mild and moderate allergic asthmatic patients improved the lung function by increasing the forced expiratory volume in 1 second (FEV 1 ), forced vital capacity (FVC), FEV 1 /FVC ratio, and forced expiratory flow (FEF) 25-75 and decreased some inflammatory factors (anti-HSP 70 and hs-CRP) in comparison to placebo [8]. In this trial the clinical symptoms of patients (including frequency of the shortness of breath during day-and nighttime, use of salbutamol spray, waking up due to asthma symptoms, and activity limitation) improved after saffron supplementation [9].…”
Section: Saffron and Asthmamentioning
confidence: 88%
“…Saffron (Crocus sativus L.) has antioxidant [5], anti-inflammatory [6], and muscle relaxant effects [7] and so has beneficial effects on asthma. Results of our clinical trial showed that saffron supplementation (100 mg of dried saffron stigma in capsules) for 8 weeks in mild and moderate allergic asthmatic patients improved the lung function by increasing the forced expiratory volume in 1 second (FEV 1 ), forced vital capacity (FVC), FEV 1 /FVC ratio, and forced expiratory flow (FEF) 25-75 and decreased some inflammatory factors (anti-HSP 70 and hs-CRP) in comparison to placebo [8]. In this trial the clinical symptoms of patients (including frequency of the shortness of breath during day-and nighttime, use of salbutamol spray, waking up due to asthma symptoms, and activity limitation) improved after saffron supplementation [9].…”
Section: Saffron and Asthmamentioning
confidence: 88%
“…Several studies have listed the significant and nonsignificant effects of C sativus L supplements on the demographic, anthropometric, and clinical characteristics of asthma [ 6 , 8 , 9 ]. Hosseini et al [ 9 ] showed that C sativus L significantly affected anti-HSP and hs-CRP factor serum levels . Moreover, they showed that it increased the pulmonary volumes FEV 1 , FVC, FEV 1 /FVC, and FEF 25%-75% [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hosseini et al [ 9 ] showed that C sativus L significantly affected anti-HSP and hs-CRP factor serum levels . Moreover, they showed that it increased the pulmonary volumes FEV 1 , FVC, FEV 1 /FVC, and FEF 25%-75% [ 9 ]. They also showed that there was no significant effect on the eosinophil count [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of saffron crocus has been clinically investigated in diabetes [180], asthma [181,182], cognitive impairment [183][184][185][186], glaucoma [187], macular degeneration related to age [188,189], sexual dysfunction in women [190] and men [191], and premenstrual syndrome [192]. These effects are out of the scope of the present thesis, therefore clinical and preclinical studies not related to the antidepressant activity are not discussed here.…”
Section: Pharmacological Activities Of Saffron Crocusmentioning
confidence: 99%